2018
DOI: 10.1016/j.buildenv.2018.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the “black box” of thermal adaptation using information entropy

Abstract: Thermal adaptation has been interpreted well by behavioral, physiological, and psychological factors, but the mechanism and interaction between the three factors remain in the "black box". This paper aims to apply the theory of general system and information entropy to investigate the quantitative relationships of the three thermal adaptation processes. Based on the database from the field survey and laboratory experiments conducted in the hot summer and cold winter climate zone of China, three typical adaptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Field data from the naturally ventilated, air‐conditioned, and mixed‐mode buildings have verified the proposed arPMV with a large reduction in the mean absolute error and a large improvement in the robustness of the thermal sensation prediction compared with the aPMV (Sections 3‐5). In the literature, there are some efforts on differentiating the three categories of thermal adaptations to explore the mechanisms of thermal adaptations 34,40,63,64 . For example, Jing 40 and Liu 64 aimed at figuring out the relative importance of the three categories of thermal adaptations using the information entropy and the analytic hierarchy process, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Field data from the naturally ventilated, air‐conditioned, and mixed‐mode buildings have verified the proposed arPMV with a large reduction in the mean absolute error and a large improvement in the robustness of the thermal sensation prediction compared with the aPMV (Sections 3‐5). In the literature, there are some efforts on differentiating the three categories of thermal adaptations to explore the mechanisms of thermal adaptations 34,40,63,64 . For example, Jing 40 and Liu 64 aimed at figuring out the relative importance of the three categories of thermal adaptations using the information entropy and the analytic hierarchy process, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are some efforts on differentiating the three categories of thermal adaptations to explore the mechanisms of thermal adaptations 34,40,63,64 . For example, Jing 40 and Liu 64 aimed at figuring out the relative importance of the three categories of thermal adaptations using the information entropy and the analytic hierarchy process, respectively. Schweiker and Wagner 34,63 determined the clothing level and metabolic rate for the PMV calculation by setting up equations for each of the three categories of thermal adaptations individually.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The linear relationship between the metabolic rate and the indoor air temperature is resulted from the physiological adaptation. Using the information entropy analysis of a large database, Jing et al [40] found that the physiological adaptation was linearly related to the indoor air temperature approximately. Since the air velocity (> 0.2 m/s) also has cooling effects [41] and is encouraged for the thermal preference and energy saving [6], Equation 1 correlates the metabolic rate to both the room air temperature and velocity linearly.…”
Section: Methods For Pmv Improvementmentioning
confidence: 99%
“…The study proposed that the active interaction of offices' internal environments with the outdoor environment will motivate further connections between occupants' thermal opinions and outdoor physical variables [26]. However, in most recent researches [11,14,[27][28][29][30][31][32], there is a lack of explanation regarding the dynamic changing characteristics of a person's behavioral adaptability to environmental changes, while there is a growing need to better understand the impact of seasonal variation on occupants' dynamic thermal comfort and using large time scales may hide the dynamic process of thermal adaptation. Therefore, obtaining detailed information such as the occupant's response to seasonal changes in climate in a large-scale survey is very challenging.…”
Section: Introductionmentioning
confidence: 99%